Annama H chondrite—Mineralogy, physical properties, cosmic ray exposure, and parent body history. (11th April 2017) - Kohout, Tomáš; Haloda, Jakub; Halodová, Patricie; Meier, Matthias M. M.; Maden, Colin; Busemann, Henner; Laubenstein, Matthias; Caffee, Marc. W.; Welten, Kees C.; Hopp, Jens; Trieloff, Mario; Mahajan, Ramakant R.; et al.
Abstract: The fall of the Annama meteorite occurred early morning (local time) on April 19, 2014 on the Kola Peninsula (Russia). Based on mineralogy and physical properties, Annama is a typical H chondrite. It has a high Ar‐Ar age of 4.4 Ga. Its cosmic ray exposure history is atypical as it is not part of the large group of H chondrites with a prominent 7–8 Ma peak in the exposure age histograms. Instead, its exposure age is within uncertainty of a smaller peak at 30 ± 4 Ma. The results from short‐lived radionuclides are compatible with an atmospheric pre‐entry radius of 30–40 cm. However, based on noble gas and cosmogenic radionuclide data, Annama must have been part of a larger body (radius >65 cm) for a large part of its cosmic ray exposure history. The 10 Be concentration indicates a recent (3–5 Ma) breakup which may be responsible for the Annama parent body size reduction to 30–35 cm pre‐entry radius.